Identify the second step in solving this equation for y : −3(y + 6) = 21 . (1 point)
Responses
Divide both sides by −3
.
Divide both sides by negative 3.
Divide both sides by 6.
Divide both sides by 6.
Subtract 6 from both sides.
Subtract 6 from both sides.
Add 6 to both sides.
Add 6 to both sides.
7 answers
Divide both sides by -3.
For which equation is the order of steps to first divide both sides by 6 and then to add 8 to both sides?(1 point)
Responses
6(x + 8) = 48
6 left parenthesis x plus 8 right parenthesis equals 48
8(x − 6) = 48
8 left parenthesis x minus 6 right parenthesis equals 48
6x − 8 = 48
6 x minus 8 equals 48
6(x − 8) = 48
Responses
6(x + 8) = 48
6 left parenthesis x plus 8 right parenthesis equals 48
8(x − 6) = 48
8 left parenthesis x minus 6 right parenthesis equals 48
6x − 8 = 48
6 x minus 8 equals 48
6(x − 8) = 48
8(x − 6) = 48
For which equation is the order of steps to first divide both sides by 2 and then to subtract 10 from both sides?(1 point)
Responses
10(x + 2) = 16
10 Left Parenthesis x plus 2 Right Parenthesis equals 16
2(x + 10) = 16
2 Left Parenthesis x plus 10 Right Parenthesis equals 16
2x + 10 = 16
2 x plus 10 equals 16
2(x − 10) = 16
Responses
10(x + 2) = 16
10 Left Parenthesis x plus 2 Right Parenthesis equals 16
2(x + 10) = 16
2 Left Parenthesis x plus 10 Right Parenthesis equals 16
2x + 10 = 16
2 x plus 10 equals 16
2(x − 10) = 16
2x + 10 = 16
What is the solution of the equation −4(z + 12) = 36 when solving for z
? (1 point)
Responses
24
24
−21
negative 21
−6
negative 6
21
? (1 point)
Responses
24
24
−21
negative 21
−6
negative 6
21
−21